Lesser toe deformity classification: A simplified approach with treatment influence. (September 2021) - Weyandt, Zachery; Capuzzi, Mark; McGlone, William; Bernatsky, Adam; Ford, Timothy
Highlights: LTDC is a simple approach to classify toe deformities. Includes common toe pathology often left out. LTDC allows improved toe deformity surgical outcome data. Brings attention to need for a lesser toe deformity classification. Abstract: Deformities of the lesser toes are one of the most commonly treated conditions by foot and ankle surgeons. Despite their frequency, a standardized classification has yet to take hold among providers. Generic nomenclature with the addition of multiple adjunctive descriptors continues to be the standard leading to international confusion. A literature review was conducted to analyze any literature and/or textbooks pertaining to lesser toe deformity classification systems. Seven sources met the inclusion criteria and were analyzed consisting of novel, modified, and previously published systems. A simplified and treatment driven lesser toe deformity classification utilized at the University of Louisville is introduced, which categorizes these deformities into one of two groups. Type 1 deformities are those isolated to the toe only and Type 2 deformities are toe deformities that include metatarsal phalangeal joint involvement. The intent of the University of Louisville Lesser Toe Deformity Classification (LTDC) is to improve communication and documentation, as well as assist surgical planning. Level of clinical evidence: 5.